2018
DOI: 10.1093/nar/gky480
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism for de novo initiation at two sites in the respiratory syncytial virus promoter

Abstract: The respiratory syncytial virus (RSV) RNA dependent RNA polymerase (RdRp) initiates two RNA synthesis processes from the viral promoter: genome replication from position 1U and mRNA transcription from position 3C. Here, we examined the mechanism by which a single promoter can direct initiation from two sites. We show that initiation at 1U and 3C occurred independently of each other, and that the same RdRp was capable of precisely selecting the two sites. The RdRp preferred to initiate at 3C, but initiation sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 46 publications
2
36
0
1
Order By: Relevance
“…1b, c). Using an established RdRp assay 13,41 , we demonstrated the characteristic RNA products of both de novo initiation (≤25 nt) and back primer (>25 nt) activities by the wt polymerase L:P (lane 6), but not the catalytically inactive polymerase L(D811A):P (lane 3) using a short trailer complementary 25 (TrC25) RNA template. The Le or TrC sequences of the genome serve as the promoters for the RSV polymerase.…”
Section: Resultsmentioning
confidence: 99%
“…1b, c). Using an established RdRp assay 13,41 , we demonstrated the characteristic RNA products of both de novo initiation (≤25 nt) and back primer (>25 nt) activities by the wt polymerase L:P (lane 6), but not the catalytically inactive polymerase L(D811A):P (lane 3) using a short trailer complementary 25 (TrC25) RNA template. The Le or TrC sequences of the genome serve as the promoters for the RSV polymerase.…”
Section: Resultsmentioning
confidence: 99%
“…Both processes are initiated by the L-P complex from a common promoter at the 3´end of the genome [17][18][19]. The polymerase initiates transcription and antigenome synthesis from two distinct sites within the same promoter, and the relative concentrations of the respective initiating NTPs can determine which initiation site the polymerase selects [20]. This, coupled with the fact that the polymerase can only engage in antigenome synthesis following accumulation of sufficient soluble N protein to encapsidate the antigenome, provides an explanation for how a polymerase molecule engaging with the genome template can become committed to either mRNA transcription versus antigenome production [21], but how transcription and replication are temporally controlled remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Given that the ebolavirus gene start signals begin with a C residue (27,28), this could reflect a preference of the polymerase for initiating with GTP. A recent study of RSV initiation showed that its polymerase has a template-independent affinity for the initiating NTPs and that this plays a role in initiation site selection (29). Thus, it is possible that ebolavirus polymerases preferentially bind GTP due to template-independent affinity, and that this affinity combined with positioning by the promoter helps guide initiation at the correct site.…”
Section: Discussionmentioning
confidence: 99%